Contribution of Information and Communication Technologies to Growth - Zhen-Wei Qiang, Christine; Pitt, Alexander; Ayers, Seth (Washington, DC: World Bank, 2013)
Thee worldwide development of information and communication technology (ICT) has accelerated dramatically over the past decade. Increased ICT production and use has the potential to influence economic growth positively. This paper focuses on the linkage between ICT and output growth and summarizes the findings in the literature on the contribution of ICT to economic growth arising from capital deepening and increases in total factor productivity. It looks at the methodologies used to assess the magnitude of the different channels through which ICT influences productivity growth, summarizes the key factors that increase and obstruct ICT expansion, and outlines the challenges developing countries face in maximizing ICT's contribution to growth. Strengthening institutions to create an environment that attracts ICT investment and promotes ICT use; exploiting network and spillover effects by creating domestic demand; and promoting "adaptation close to use" to match local capacity and local needs have been identified as policies to surmount these challenges.